PERANCANGAN SISTEM PENGKREDITAN PADA SHOWROOM MOBIL ALYA MOTOR - M. Ibnu Safari; Marviyana Marviyana; Irfan Setiawan (UNIVERSITAS RAHARJA, 2016)
This study aims to analyze the computerized system is precise and accurate. But in reality it is sometimes not in accordance with the wishes and expectations to be achieved, due to the limited system is computerized so that experienced weakness in the calculation of accounts receivableapplications used on the Motor Car Showroom Alya. With the lack of a computerized system, then a lot of problems that occur, especially in preparing sales reports and determine the credit limits on Alya Motor Car Showroom. Among others, the absence of data input system creditreport so it is difficult for decision-making, making the report still has not produced data precise and accurate because of the frequent occurrence of errors in the calculation of entry and exit of money, and often resulted in the difference / no balance consequently the reporting process soimprecise time. Using a simulation system of credit. The results obtained after trial stage of implementation of the system was satisfactory because it can meet the needs of users at once facilitate process credit transactions by customers.